Sukuk Linked Waqf Perspective Abu Zahra’s Maqashid Sharia Model as Financial Investment Product - Ahmad Syaichoni; Suminto Suminto (UIN Mataram, 2021)
Indonesia is a country where the majority of the population is Muslim. One of the potentials that Indonesia has with its Muslim community is the waqf order. This great potential of waqf certainly provides a positive side for the state in the context of the welfare of its people. To improve people’s welfare through the potential of waqf, the government through Otoritas Jasa Keuangan (OJK) makes a sharia investment instrument that is linked to waqf, namely the Sukuk Linked Waqf product. This product is a combination of Sukuk and waqf. The emergence of this product is expected to be able to achieve the great potential of waqf and expand the market share of Islamic finance indirectly, the Sukuk Linked Waqf product is a product that is expected to increase sharia financial inclusion. The method used is a literature review of maqashid sharia and Sukuk. This study used critic analysis and content analysis to investigate the theory of maqashid sharia and Sukuk. The results showed that Sukuk Linked Waqf based on Abu Zahra’s maqashid sharia model is a financial investment product that aims to bring benefits. The benefits, in this case, are in the form of welfare for humans in terms of economic improvement. Whit the emergence of this product, the road to the welfare of the people becomes more real.